Operation of the Hybrid Photovoltaic-Battery System on the Electricity Market—Simulation, Real-Time Tests and Cost Analysis - Robert Małkowski; Marcin Jaskólski; Wojciech Pawlicki (Energies, 2020)
This paper presents research on a hybrid photovoltaic-battery energy storage system, declaring its hourly production levels as a member of a balancing group submitting common scheduling unit to the day-ahead market. It also discusses the variability of photovoltaic system generation and energy storage response. The major research questions were whether the operation of a hybrid photovoltaic-battery energy storage system is viable from the technical and economic viewpoint and how to size battery energy storage for that purpose. The DIgSILENT PowerFactory environment was used to develop the simulation model of postulated hybrid system. Then, tests were conducted on real devices installed in the LINTE^2 laboratory at Gdańsk University of Technology, Poland. Firstly, power generation in the photovoltaic system was modeled using hardware in the loop technique and tested in cooperation with emulated photovoltaic and real battery energy storage system (lithium-ion battery, 25 kWh). Secondly, a real photovoltaic power plant (33 kW) and real battery energy storage were applied. The results obtained from laboratory experiments showed that market operation of hybrid photovoltaic-battery energy storage system is feasible. However, developing a control strategy constitutes a great challenge, as the operator is forced to intervene more frequently than the simulation models indicate in order to keep the parameters of battery storage within accepted ranges, especially in view of a sudden weather breakdown. Levelized cost of electricity from photovoltaic-battery energy storage system varied from 314 to 455 $/MWh, which has proven to be from two to three times higher than the current annual average day-ahead market price in Poland.